Synthesis of phased array antenna for side lobe level reduction using the differential evolution algorithm - Tej, Ravi; Kavya, K. Ch. Sri; Kotamraju, Sarat K. (International journal of speech technology, 2020)
In this paper, we synthesis an array consisting of uniformly excited unequally spaced elements for reducing SLLs. A globally optimal solution for the array elements phase and position is determined by using a differential evolutionary algorithm for a given radiation pattern. Reduced side-lobe levels are observed with position-phase synthesis. The obtained results are compared with the possible two cases i.e., uniform amplitude equal phase (variable position-control) and uniform amplitude unequal phase (variable phase-control). The obtained results justify that the position-phase synthesis technique is not only reduces the side-lobe levels to (− 25.28) dB, but also preserves the advantages of both variable position-controlled synthesis and variable phase-controlled synthesis with a minimum number of array elements.